Autoantibodies targeting neuronal proteins as biomarkers for neurodegenerative diseases - Kocurova, Gabriela; Ricny, Jan; Ovsepian, Saak V (Theranostics, 2022)
Neurodegenerative diseases (NDDs) are associated with the accumulation of a range of misfolded proteins across the central nervous system and related autoimmune responses, including the generation of antibodies and the activation of immune cells. Both innate and adaptive immunity become mobilized, leading to cellular and humoral effects. The role of humoral immunity in disease onset and progression remains to be elucidated with rising evidence suggestive of positive (protection, repair) and negative (injury, toxicity) outcomes. In this study, we review advances in research of neuron-targeting autoantibodies in the most prevalent NDDs. We discuss their biological origin, molecular diversity and changes in the course of diseases, consider their relevance to the initiation and progression of pathology as well as diagnostic and prognostic significance. It is suggested that the emerging autoimmune aspects of NDDs not only could facilitate the early detection but also might help to elucidate previously unknown facets of pathobiology with relevance to the development of precision medicine.
Keywords: Neurons; Fluid biomarkers; lidé; proteiny; immunoglobins; autoimmunity; dementia; differential diagnosis; autoimunita; Autoimmunity; Humans; biologické markery; neurony; Neurodegenerative Diseases; neurodegenerativní nemoci; Biomarkers; Proteins; Autoantibodies; autoprotilátky